Retained Abdominal Gallstones After Laparoscopic Cholecystectomy: A Systematic Review - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Aim: The aim of this study is to make a systematic review of high-quality published trails regarding the complications of retained gallstones after laparoscopic cholecystectomy for cholelitiasis. Materials and Methods: Medline search from 1987 to 2013 was done. Nine studies with >500 LCs which reported retained gallstones and perforated gallbladders were analyzed systematically. Results: Of 536 listed reports including case reports, clinical trials, reviews, journal articles, and meta-analytic reports; 9 studies each reporting >500 LCs which reported the incidence of perforated gallbladders and spilled stones were found. The number of operations, the number of perforated gallbladders, the number of patients who had gallstone spillage, and the postoperative complications were searched in these studies and the strongest and weakest aspects of the articles were discussed. Conclusions: Retained abdominal gallstones can cause various postoperative problems including extra-abdominal complications. In case of perforation of the gallbladder during laparoscopic cholecystectomy, spilled gallstones should be collected to prevent further complications but conversion to open surgery is not mandatory.
Keywords: laparoscopic cholecystectomy; gallbladder perforation; retained gallstones; GALLBLADDER PERFORATION; SPILLED GALLSTONES; COMPLICATIONS; MANAGEMENT